Health Coaching in Improving Drug Adherence in Pulmonary Tuberculosis Patients: A Systematic Review - Muhith, Abdul; Hidayatullah, Achmad; Zahroh, Chilyatiz (Chakra Brahmanda Lentera Institute, 2024)
Background: The problem in patients with pulmonary tuberculosis is non-compliance with treatment and patients who are tired of treatment, sometimes patients decide to stop treatment because they have been treated for too long and patients start to get bored because they do not get better. Aims: The purpose of this study conducted a systematic review related to the effect of Health Coaching in Improving Drug Adherence in Pulmonary Tuberculosis Patients. Method : This research article uses a systematic review design with a standard systematic review approach (PRISMA) to carry out systematic analysis. Results and Conclusion. The provision of Health Education and Health Coaching can significantly improve medication adherence in pulmonary tuberculosis patients.